2010
DOI: 10.1097/wox.0b013e3181d25e8e
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment in Severe Asthma

Abstract: BackgroundIn Brazil, like many other low- to middle-income countries, most asthmatic patients cannot afford the medication necessary to prevent exacerbations. The reference clinic of the Programme for Asthma Control in Bahia (ProAR; Salvador-Bahia) offers free medical care, pharmaceutical assistance (inhaled medication) and patient education. The reference clinic is accessible to all the population of Salvador and the Programme is targeted on severe asthma.ObjectiveThe aim of the present study was to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 21 publications
0
8
0
4
Order By: Relevance
“…Factors related to a lack of asthma control include non-adherence to treatment, a precipitous reduction in the dose of inhaled corticosteroid, carelessness in maintaining environmental controls, and comorbidities. ( 19 ) In another ProAR study, ( 20 ) correct inhaler technique was found to be associated with asthma symptom control. The authors suggested that the inhaler techniques employed by asthma patients should be evaluated, on a regular basis, by a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Factors related to a lack of asthma control include non-adherence to treatment, a precipitous reduction in the dose of inhaled corticosteroid, carelessness in maintaining environmental controls, and comorbidities. ( 19 ) In another ProAR study, ( 20 ) correct inhaler technique was found to be associated with asthma symptom control. The authors suggested that the inhaler techniques employed by asthma patients should be evaluated, on a regular basis, by a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 97%
“…An earlier study identified certain factors as being predictive of poor adherence to treatment among patients enrolled in the ProAR, ( 19 ) including adverse events, great distances between the patient residence/workplace and the health care facility, transportation difficulties, and short dosage intervals for prescriptions involving multiple doses. Factors related to a lack of asthma control include non-adherence to treatment, a precipitous reduction in the dose of inhaled corticosteroid, carelessness in maintaining environmental controls, and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most commonly reported barriers to long-term controller medication for asthma include: fear of adverse effects, addiction, or dependence to medication; belief that the medication does not help or is not necessary; concerns about a diminishing effectiveness of medication over time; preference for alternative asthma management; sense of only an intermittent need for medication; inconvenient dosage regimens; inadequate knowledge of the medication and/or the disease; cost of the medication; stigmatization of the affected individual; dislike of the provider; medical comorbidity; and the lack of social support [ 13 - 19 ]. In contrast, previously identified facilitators are: simple dosage regimens (e.g., one-daily dose); patients’ knowledge related to the medication and the disease; access to high-quality personalized health care; coping with the disease; appropriate asthma self-management; and, possessing a written action plan [ 16 , 17 , 19 - 21 ]. A first taxonomy of facilitators of physicians’ prescription behavior in the acute care setting, which included 5 domains (knowledge, attitude, and beliefs; operationalization of guidelines; choice of medication; parent or patient-related factors; and setting-related factors), was developed [ 22 ].…”
Section: Introductionmentioning
confidence: 99%